Raia Divisória ou Raia Socioambiental?: uma redefinição baseada na análise da paisagem através do sistema GTP - Souza, Reginaldo José de [UNESP] (2015)
Dividing or social environmental 'borderland' ('raia')? This question appears from my concern around the conceptual definition of the contact zone established by the territories of the extreme southwest of 'São Paulo' state, northwest of 'Paraná' state, and southeast of 'Mato Grosso do Sul' state. The 'São Paulo-Paraná-Mato Grosso do Sul' 'borderland' ('raia'), already was target of the several approaches, from the climatology to the geography of agricultural spaces. The 'Dividing borderland' idea was developed by Passos (2005, 2006, 2007), where this author defined 'Dividing borderland' as a intergradation area where the geographical processes are manifested according a logical objective discontinuity of the landscape, in a context of relative physiognomic homogeneity - geological substratum, relief, soil and vegetation. The occupation of the territory occurred differently among southwest of 'São Paulo' state, northwest of 'Paraná' state and southeast of 'Mato Grosso do Sul' state, after the first decades of the twentieth century. In the southwest of 'São Paulo' state, the occupation of the territory was motivated by coffee plantation and railroad spread; illegal appropriation of forest reserves and aggressive deforestation. The northwest of 'Paraná' state was contemplated by a modern colonization conception, whose rural lots subdivision happened to flowing the economy. In the southeast of 'Mato Grosso do Sul' state there was a capitalization spread, observed mainly in the neighboring areas and previous occupation areas...